LATERALITY OF NYSTAGMUS IN TRAUMATIC BRAIN INJURY (TBI): DIAGNOSTIC AND NEUROANATOMICAL CONSIDERATIONS - Karimov Bakhodirjon Alisher o’g’li; Jiyanov Ibrohim Abdujabbarovich; Karimbayev Shukhratjon Talabayevich. (Scholar Express Journals, 2025)
Traumatic Brain Injury (TBI) frequently presents with neuroophthalmological manifestations, among which nystagmus serves as a dynamic and often underappreciated clinical sign. The direction (or side) of nystagmus—especially in the acute phase—can offer critical clues about the localization, nature, and extent of both central and peripheral vestibular dysfunctions. This article explores the laterality of nystagmus within the complex neuroanatomical landscape affected by TBI and evaluates how this sign can help differentiate between brainstem, cerebellar, and peripheral injuries.
Keywords: Traumatic Brain Injury; Nystagmus; Laterality